2018
DOI: 10.1038/s41426-018-0103-4
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional seroepidemiology study of EV-D68 in China

Abstract: Enterovirus 68 (EV-D68) is associated with respiratory diseases, such as acute upper respiratory tract infections (URTIs), lower respiratory tract infections (LRTIs), pneumonia, neurological diseases, and acute flaccid myelitis (AFM). In recent years, there have been global outbreaks of EV-D68 epidemics. However, there is no effective vaccine against EV-D68, and the understanding of the seroprevalence characteristics of EV-D68 is limited. To evaluate the epidemiological features of this emerging infection in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
1
22
2
Order By: Relevance
“…The EV-D68 seroprevalence rate was approximately 59% among children younger than 15 years old in China, and it was positively correlated with age among 1-year-old (10%) to 15-year-old (92%) children [18]. The seroprevalence rates of adults approach 100% in China, the United States, the United Kingdom, the Netherlands and Taiwan [10][11][12][13]18]. We thus listed and compared EV-D68 serostatus among different countries in Table 3.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The EV-D68 seroprevalence rate was approximately 59% among children younger than 15 years old in China, and it was positively correlated with age among 1-year-old (10%) to 15-year-old (92%) children [18]. The seroprevalence rates of adults approach 100% in China, the United States, the United Kingdom, the Netherlands and Taiwan [10][11][12][13]18]. We thus listed and compared EV-D68 serostatus among different countries in Table 3.…”
Section: Plos Onementioning
confidence: 99%
“…The above finding could imply that EV-D68 has spread extensively worldwide, although only a limited number of severe cases have been reported. The cutoff for EV-D68 seropositivity was �1:8 [12,13,18], except in the UK study, which used a titer of >1:16 as the cutoff [12]. � The name or genotype of the viral strain was used for neutralizing antibody, and reverse genetics with Fermon strain was used to produce the EV-D68 virus (Synthetic) in the China study.…”
Section: Plos Onementioning
confidence: 99%
“…Evidence for continuous antigenic evolution. Given that most EV-D68 cases are pediatric (Holm-Hansen et al, 2016) and that almost everyone has high EV-D68 titers by the age of ten Karelehto et al, 2019;Sun et al, 2018;Xiang et al, 2017), one might expect that selection for antigenic change is of minor importance for the molecular evolution of EV-D68. However, we found rapid evolution in putative neutralizing epitopes, including the previously studied BC-and DE-loops (Du et al, 2015;Dyrdak et al, 2019).…”
Section: Bc-loopmentioning
confidence: 99%
“…The great majority of reported EV-D68 cases are pediatric (Holm-Hansen et al, 2016), and sero-positivity to EV-D68 increases rapidly during childhood, reaching ubiquity in adults Karelehto et al, 2019;Sun et al, 2018;Xiang et al, 2017). Relatively little is known about immunity to EV-D68, but infection appears to elicit long-lasting strain-specific immunity, as evidenced by the high prevalence among adults of neutralising antibodies to the prototype Fermon strain from 1962 Karelehto et al, 2019;Smura et al, 2010;Xiang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The EV-D68 seroprevalence rate is around 59% in China and anti-EV68 neutralizing antibodies titer increase with time according to previous reports. 34,35 Another 2014 study that included 319 participants aged between six to 35 months old in Jiangsu, China found that the seropositive rate increased from 49.2% in 2012 to 60.5%. 36 Adults are widely infected with EV-D68 and have higher seroprevalence rates.…”
Section: Seroprevalencementioning
confidence: 99%